2016
DOI: 10.1200/jco.2015.63.6738
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Loss in Patients Who Received Cranial Radiation Therapy for Childhood Cancer

Abstract: Purpose Patients treated with cranial radiation therapy (RT) are at risk for sensorineural hearing loss (SNHL). Although SNHL is often characterized as a delayed consequence of anticancer therapy, longitudinal reports of SNHL in childhood cancer survivors treated with contemporary RT are limited. We report the incidence, onset, severity, and long-term trajectory of SNHL among children receiving RT. Potential risk factors for SNHL were also identified. Patients and Methods Serial audiologic testing was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
110
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(118 citation statements)
references
References 37 publications
3
110
4
1
Order By: Relevance
“…Damage to the hearing apparatus with resultant sensorineural hearing loss (SNHL) is a common adverse event after RT [175177], occurring in up to 43% of irradiated HNC patients. Its incidence is increased to 17–88% when RT is combined with cisplatin [178].…”
Section: Hearing Lossmentioning
confidence: 99%
“…Damage to the hearing apparatus with resultant sensorineural hearing loss (SNHL) is a common adverse event after RT [175177], occurring in up to 43% of irradiated HNC patients. Its incidence is increased to 17–88% when RT is combined with cisplatin [178].…”
Section: Hearing Lossmentioning
confidence: 99%
“…For example, hearing loss may require supports in the school environment for this population. Studies report the prevalence of sensorineural hearing loss associated with cranial radiation at 14%, while prevalence of cisplatin‐related loss ranges from 20% to 67% . Hearing loss is associated with declines in cognitive function and diminished academic outcomes in the childhood cancer population .…”
Section: Discussionmentioning
confidence: 99%
“…Studies report the prevalence of sensorineural hearing loss associated with cranial radiation at 14%, while prevalence of cisplatin-related loss ranges from 20% to 67%. 34,35 Hearing loss is associated with declines in cognitive function and diminished academic outcomes in the childhood cancer population. 36,37 School absenteeism due to clinic visits for provision of cancer treatment or treatment side effects including fatigue is often overlooked for its impact on school functioning and achievement.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of 23,000 survivors of childhood cancer who were diagnosed between 1970 and 1999 demonstrated an increased incidence of hearing loss over time, even as the incidence of several other late effects decreased . Prior studies have suggested that many childhood and young adult cancer survivors have severe hearing loss that could benefit from hearing aids and that, for some, hearing loss worsened years after treatment …”
Section: Introductionmentioning
confidence: 99%
“…4 Prior studies have suggested that many childhood and young adult cancer survivors have severe hearing loss that could benefit from hearing aids and that, for some, hearing loss worsened years after treatment. 5,6 Unfortunately, the social consequences of hearing loss can be profound. In older adults, hearing loss has been associated with depression, cognitive impairment, and social isolation.…”
Section: Introductionmentioning
confidence: 99%